2015
DOI: 10.1093/mnrasl/slv142
|View full text |Cite
|
Sign up to set email alerts
|

The impact of enhanced iron opacity on massive star pulsations: updated instability strips

Abstract: Recently, Bailey et al. (2015) made a direct measurement of the Iron opacity at the physical conditions of the solar tachocline. They found that the wavelength-integrated Iron opacity is roughly 75% higher that what the OP and OPAL models predict. Here, we compute new opacity tables with enhanced Iron and Nickel contributions to the Rosseland mean opacity by 75% each, and compute three dense MESA grids of evolutionary models for Galactic O-and B-type stars covering from 2.5 to 25 M from ZAMS until T eff = 10 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Recently, Moravveji (2016) showed that a 75% increase in the Iron and Nickel monochromatic opacities explains the position of two confirmed β Cep and eight confirmed hybrids on the Kiel diagram, which could not be explained before. The increase resulted from the direct laboratory Iron opacity measurement of Bailey et al (2015), which was later confirmed by the numerical simulations of Nagayama et al (2016).…”
Section: Asteroseismic Modelsmentioning
confidence: 94%
See 3 more Smart Citations
“…Recently, Moravveji (2016) showed that a 75% increase in the Iron and Nickel monochromatic opacities explains the position of two confirmed β Cep and eight confirmed hybrids on the Kiel diagram, which could not be explained before. The increase resulted from the direct laboratory Iron opacity measurement of Bailey et al (2015), which was later confirmed by the numerical simulations of Nagayama et al (2016).…”
Section: Asteroseismic Modelsmentioning
confidence: 94%
“…The spectroscopic properties of KIC 7760680 from HERMES (Raskin et al 2011) high-resolution spectra are T eff = 11650 ± 210 K, =  g log 3.97 0.08 dex, [M/H] = 0.14 ± 0.09, and =  v i sin 62 5 km s −1 . The inferred T eff and g log place KIC 7760680 at the low-mass end of the SPB instability strip (Pamyatnykh 1999;Moravveji 2016). Pápics et al (2015) identified a series of  = 36 lowfrequency modes with periods between P 1 ± σ 1 = 0.86930 ± 0.00002 and P 36 ± σ 36 = 1.46046 ± 0.00004 days (their Table 1).…”
Section: Asteroseismic Observables Of Kic 7760680mentioning
confidence: 99%
See 2 more Smart Citations
“…They used models dependent upon opacities and the known optical depths of the interstellar clouds to determine its fractal dimension. Another example is the work of Moravveji (2016), whose opacity simulations, comparing measured to measured spectra, concluded that nickel ions produce an enhancement of the opacity.…”
Section: Introductionmentioning
confidence: 99%